(Des)continuidade espacial da precipitação pluvial no Estado de Mato Grosso – Brasil - Oliveira, Janiel Lopes de (2024)
Rainfall is an atmospheric variable that presents great temporal and spatial variability and is important for environmental sustainability. There is a continued search to identify and understand spatial dynamics and rainfall trends over time, and understand the relationship of this variable with other factors in the physical environment, as well as predict future situations based on sets of historical records. In this context, this research was carried out to identify the spatial continuity of rainfall in the state of Mato Grosso, as well as to estimate average precipitation values for non-sampled locations in the period from 1985 to 2020. From this perspective, historical series from 109 rainfall stations in the state were used. National Water and Basic Sanitation Agency (ANA), taking into account the criteria of the World Meteorological Organization (WMO), with records of at least 30 consecutive years and a failure rate of 10% of the data. In the treatment and processing of data, Statistics and Geostatistics resources, spreadsheet applications and the use of Geographic Information System (GIS) tools were used. The research followed a design starting from the tabulation and correction of flaws in the historical series, followed by descriptive statistics, frequency distribution and data preparation according to geostatistics precepts, modeling using experimental semivariograms, interpolation with ordinary kriging and data analysis of average annual precipitation in different scenarios. In the results, the descriptive statistics stand out where the monthly averages from November to March range from 136.2 to 296.7 mm, and July had the lowest average for the period with 7.1 mm. For annual averages, the maximum value was 1,971.6 mm in 2013, and the minimum was 1,511.4 mm in 2015. As for frequency distribution, 81.48% of precipitation had averages ranging from 1,373.3 mm to 2,159.6 mm. As for the correlation coefficient (r) between the dependent (y) and independent (x) variables, the values were: 0.681 (rain and latitude) and 0.483 (rain and longitude). However, when calculating the dependence between x and y, the coefficient of determination r² was 0.667, the standard error was 165.87. In the spatial continuity modeled with semivariogram for the regional scale, the range of the phenomenon was 336.1 km, with r² of 0.973, IDE equivalent to 0.14, and cross validation with r² of 0.996. At the local scale, the range was 174.3 km, with r² of 0.995, IDE equivalent to 0.04, cross-validation with an r² value of 0.253. In kriging, for regional and local scales, more than 36,000 values were estimated, representing the average annual precipitation for all municipalities in Mato Grosso, specifically those that do not have rainfall stations. It is worth highlighting the estimated averages for the municipalities of Colniza–MT, with an estimated value of 2,406.03 mm (maximum) and Alta Taquari–MT, with 1,135.84 mm (minimum). The analysis of data in different scenarios had indicators and average deviations of rainfall data when relating periods of 12 years to a period of 36 years, indicating behaviors that change in time intervals shorter than 30 years.